Comparison study of mechanical and dynamic vibration properties of hole defect introduced in hybrid polymer composite. (2020) - Rajkumar, K.; Ramraji, K.; Hariprakash, V.P.; Gnanavelbabu, A.
Abstract: The need for hybrid composites has increased because it includes the advantages both of synthetic glass and natural fibers. In this research work, a hybrid composite has been developed using a glass and coir fiber which has been subjected to moisture, tensile with and without the hole, flexural and dynamic properties. The glass fiber-coconut coir-glass fiber (G-C-G) hybrid composite was made by hand layup technique. The dynamical properties of tensile and open-hole tensile composites were measured by a free vibration technique. SEM analysis on fractured surfaces of the composite was also performed. The results showed that there was an appreciable rise in the moisture absorption capacity of the composites. Tensile testing showed that there was a decrease in tensile strength and modulus with increases in center hole diameter. Results of the fracture study indicated that the fiber-matrix interface improved with fiber treatment. The mechanical properties of hybrid composites were abruptly decreased with a hole diameter of 6 mm. The damping ratio and natural frequency of composite without tensile hole show higher value due to undisturbed in fiber strength.